2008
DOI: 10.1111/j.1447-0756.2008.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and prevalence of psychiatric disorders among patients awaiting surgery for suspected ovarian cancer

Abstract: The above findings demonstrate that patients with suspected ovarian cancer experience a high level of anxiety. Physicians should be aware of the risk of adjustment disorder in these patients. Additionally, ovarian cancer patients need psychological assessment during the course of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Results from previous studies of anxiety levels in cancer patients seem to be inconsistent. Sukegawa et al (2008) demonstrated that the state-anxiety score of patients awaiting surgery for suspected ovarian cancer was higher than the general Japanese population (STAI-S, 49.5 ± 10.30 vs. 36.6 ± 9.06). Tagay et al (2006) demonstrated that the anxiety scores for German DTC patients undergoing short-term hypothyroidism (HADS-A score, 8.6 ± 2.8) exceeded the borderline levels (8 score).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Results from previous studies of anxiety levels in cancer patients seem to be inconsistent. Sukegawa et al (2008) demonstrated that the state-anxiety score of patients awaiting surgery for suspected ovarian cancer was higher than the general Japanese population (STAI-S, 49.5 ± 10.30 vs. 36.6 ± 9.06). Tagay et al (2006) demonstrated that the anxiety scores for German DTC patients undergoing short-term hypothyroidism (HADS-A score, 8.6 ± 2.8) exceeded the borderline levels (8 score).…”
Section: Discussionmentioning
confidence: 91%
“…Sukegawa et al . () demonstrated that the state‐anxiety score of patients awaiting surgery for suspected ovarian cancer was higher than the general Japanese population (STAI‐S, 49.5 ± 10.30 vs. 36.6 ± 9.06). Tagay et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A systematic review of longitudinal anxiety in ovarian cancer patients, published in 20 1 5, 20 featured 7 studies with labeled “pretreatment” baseline anxiety levels, only 1 of which actually reported preoperative baseline anxiety, and consisted of 27 patients total. 21 …”
Section: Commentmentioning
confidence: 99%
“…Se han realizado diversos estudios acerca del estado de ansiedad en estos pacientes (3,4) , y una variedad de intervenciones para lograr un efecto en la reducción de la ansiedad, el dolor y el estrés (5)(6)(7) . Estudios muestran que hay una fuerte correlación entre la ansiedad y la depresión (4,8) y entre la incertidumbre y la ansiedad, es decir, a mayor nivel de incertidumbre mayor ansiedad (9) . Con todo, la incertidumbre es un componente común en una situación de enfermedad y probablemente aumenta en el momento prediagnóstico (9,10) .…”
Section: Introductionunclassified